Associations between forest vertical structure and habitat preferences of black-and-white snub-nosed monkeys (Rhinopithecus bieti) in high-elevation environments - Zhipang Huang; Yuling Chen; Haitao Yang; Yihao Fang; Kai Cheng; Hongcan Guan; Cyril C. Grueter; Wen Xiao; Qinghua Guo (Ecological Informatics)
Understanding how wildlife behavior relates to habitat characteristics is essential for ecology and conservation, particularly in remote, structurally complex landscapes. In this study, we examine seasonal and behavior-specific habitat preferences in black-and-white snub-nosed monkeys (Rhinopithecus bieti), an endangered primate endemic to high-elevation forests in Yunnan, China. We combined long-term behavioral observations (2008–2018) with UAV-based LiDAR data on forest structure (collected in 2022–2023), and camera trap data on human and wildlife activity (2017–2018), to assess how these factors are associated with space use across different behaviors and seasons. Using machine learning models, we identified structural and disturbance-related attributes that were consistently associated with R. bieti behavior at the home-range scale. Vertical forest structure, particularly canopy height and vegetation layering, showed strong associations with foraging and sleeping locations across both wet and dry seasons. These patterns varied depending on behavioral context, supporting the idea that R. bieti adjusts its space use in response to seasonal and structural variation. Human and livestock presence were also negatively associated with habitat use during feeding and movement. While our findings align with established ecological expectations for semi-arboreal primates, they provide one of the first fine-scale, spatially explicit analyses of habitat preferences in R. bieti. We acknowledge the temporal mismatch between datasets as a limitation, and interpret our results conservatively as correlational. Nonetheless, this study highlights the value of combining behavioral, structural, and disturbance data to inform habitat conservation in montane forest ecosystems.